Ultrathin copper foil pinhole testing method
By using a translucent lining plate on ultra-thin copper foil for high-temperature pressing and using light transmission method to detect pinholes, the problem of difficulty in quickly positioning ultra-thin copper foil pinholes in the prior art is solved, and fast and accurate large-area detection is achieved.
Patent Information
- Application Number
- CN202411994392.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing optical microscopes or image processing technologies are difficult to quickly and widely position the pinholes on ultra-thin copper foil, resulting in difficulty in detection.
The liner plate made of a material that is light-transmitted and softened at high temperature is pressed with the copper foil at high temperature to form a test unit, and the number and position of pinholes on the surface of the copper foil are detected under a high temperature vacuum environment by light transmission.
It realizes rapid and large-scale positioning of pinhole positions on ultra-thin copper foil, improves detection accuracy and repeatability, and satisfies the judgment of large-area pinhole conditions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil physical property detection, in particular to a method for testing pinholes in ultra-thin copper foil. Background Art
[0002] As an important part of the electronic materials field, the copper foil industry has been undergoing significant changes and developments in recent years, driven by both technological innovation and market demand. Among them, one of the most significant trends is the accelerated development of copper foil towards the ultra-thin field.
[0003] Ultra-thin copper foil is widely used in various fields due to its excellent conductivity, good flexibility and high strength. In the field of lithium-ion batteries, ultra-thin copper foil as a negative electrode current collector can significantly improve the energy density and cycle performance of the battery; in the field of 5G communications, ultra-thin copper foil can meet the needs of high-frequency and high-speed signal transmission and improve communication quality and stability; in addition, in the fields of flexible electronics and wearable devices, ultra-thin copper foil also plays an irreplaceable role.
[0004] The use of ultra-thin copper foil has significant advantages for both the lithium battery industry and the electronic circuit industry. For lithium battery copper foil, by reducing the thickness of the copper foil, the amount of active material can be increased while the volume of the battery cell remains unchanged, thereby increasing the thickness of the slurry coating and improving the energy density of the battery cell. For example, compared with 8-micron copper foil, the energy density of 6-micron and 4.5-micron copper foils increased by 5.11% and 8.82% respectively.
[0005] For electronic circuit copper foil, as electronic products become increasingly miniaturized, lightweight and high-performance, the thickness of traditional copper foil can no longer meet the thin and light design requirements of modern electronic equipment. Therefore, engineers have continuously reduced the thickness of copper foil by improving production processes, such as using electrolysis and calendering methods. Currently, they are able to produce ultra-thin copper foil with a thickness of only a few microns.
[0006] During the production process of ultra-thin copper foil, pinholes may appear on the surface of the copper foil due to factors such as unsatisfactory electrolyte filtration, the generation of bubbles or heterogeneous crystals, and uneven grain size during the electroplating process. These pinholes not only affect the conductivity and mechanical strength of the copper foil, but may also cause quality defects such as resin penetration, line loss, and open circuits during subsequent processing, thereby affecting the performance and reliability of the entire electronic product. In addition, the pinhole problem of electrolytic copper foil will become more and more prominent as the thickness of the copper foil continues to decrease. Due to the randomness of the number and location of pinholes, and the extremely poor wrinkle resistance of ultra-thin copper foil itself, traditional optical microscopes or image processing technologies are difficult to quickly locate pinhole problems over a large range. This brings considerable difficulties to the pinhole detection method of copper foil. Summary of the invention
[0007] The invention provides a method for testing pinholes in an ultra-thin copper foil, which can solve the problem that it is difficult for existing optical microscopes or image processing technologies to quickly and widely locate the positions of pinholes on the ultra-thin copper foil.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for testing pinholes in ultra-thin copper foil, comprising the following steps: S1: Select a copper foil of standard size and place it flat between two lining boards to form a test unit. The lining boards are made of a light-transmitting material that can be softened at high temperatures. The copper foil between the layers can be observed through any side of the lining boards on both sides; S2: Cover the upper and lower sides of the test unit with pressing plates, put it into a high-temperature vacuum press, and apply pressure to the upper and lower sides of the test unit in a high-temperature vacuum environment; S3: Take the test unit out of the high-temperature vacuum press and cool it down, remove the pressing plate, and place the test unit together at the window on the dark box with a built-in light source, so that the light from the window passes through the copper foil, and the number and position of pinholes on the surface of the copper foil are obtained by testing and statistically analyzed.
[0009] Preferably, the lining plate is made of polyethylene or polycarbonate, which has low material cost and can meet the requirements of light transmission and high-temperature softening of the lining plate.
[0010] Preferably, the light transmittance of the lining plate is greater than 50%, and the surface flatness is less than 0.03 mm, ensuring that light and sight can be seen through. The small surface flatness can reduce wrinkles and deformation on the surface of the copper foil 3.
[0011] Preferably, when the test unit and the pressing plate are placed together in a high-temperature vacuum press, high-temperature resistant cushions are placed on the upper and lower sides thereof, and the high-temperature resistant cushions can prevent the pressure of the high-temperature vacuum press from damaging the liner and the copper foil product.
[0012] Preferably, in step S2, the test unit includes a heating stage and a heat preservation stage in the high-temperature vacuum press, thereby ensuring that the liner in the test unit can be fully softened and fully fit the surface of the copper foil at a stable temperature.
[0013] Preferably, in step S3, the copper foil is placed on the window with the front side facing up and the back side facing up in turn for testing, and the number and position of the pinholes on the front and back sides of the copper foil are compared. The number and position of the pinholes can be verified by comparing the front and back sides of the copper foil.
[0014] Preferably, the size of the window is smaller than that of the copper foil, so as to prevent the light source from being refracted through the side and affecting the pinhole judgment.
[0015] Preferably, the window is arranged at the top of the dark box, and light sources are installed on the inner side walls and bottom wall of the dark box. The window at the top is convenient for placing and moving the test unit. The light source is arranged in this way to produce more uniform light emitted from the window, reduce reflections, and have no dead angles.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The operation is simple. A light-transmitting liner is used to press the copper foil at high temperature. The copper foil is packaged between the two liner boards by high-temperature flat pressing, using the characteristics of the special liner to soften at high temperature and solidify at room temperature. This not only ensures the cleanliness of the sample to be tested, but also prevents the ultra-thin copper foil from wrinkling due to external force and affecting the test. The light transmission method is used to quickly determine the position and number of pinholes. It can meet the repeated testing requirements of samples, improve the repeatability and reproducibility of the test process, and improve the process capability of the measurement system. It can determine the situation of large-area pinholes. The large-area pad and pressure plate placed on the dark box can be used to detect the pinhole situation of large-area copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a flow chart of the testing method of the present invention; Figure 2 It is a schematic diagram of the combination of the test unit and the pressing plate of the present invention; Figure 3 It is a test schematic diagram of the present invention; Figure 4 It is a structural diagram of a dark box of the present invention.
[0018] Reference numerals: 1. Pressing plate, 2. Lining plate, 3. Copper foil, 4. Dark box, 5. Window, 6. Test unit, 7. Light source. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0020] The present invention aims to solve the problem that the existing optical microscope or image processing technology is difficult to quickly and widely locate the pinhole position on the ultra-thin copper foil. Figure 1-4 As shown, the following technical solution is provided: a method for testing pinholes in ultra-thin copper foil, comprising the following steps: S1: Select a copper foil 3 of standard size and place it flat between two lining boards 2 to form a test unit 6. The lining boards 2 are made of a light-transmitting material that can be softened at high temperatures. The copper foil 3 between the layers can be observed through any side of the lining boards 2 on both sides. S2: Cover the upper and lower sides of the test unit 6 with the pressing plate 1, put it into a high-temperature vacuum press, and apply pressure to the upper and lower sides of the test unit 6 in a high-temperature vacuum environment; S3: Take the test unit 6 out of the high-temperature vacuum press for cooling, remove the pressing plate 1, and place the test unit 6 together at the window 5 on the dark box 4 with a built-in light source, so that the light from the window 5 passes through the copper foil 3, and the number and position of pinholes on the surface of the copper foil 3 are obtained by testing and statistically analyzed.
[0021] Specifically, generally speaking, copper foil products are used for the transmission of circuit signals and pinholes are not allowed. Especially in the electronic circuit industry, the presence of pinholes can easily cause circuit disconnection. For large quantities of copper foil products, the criteria for determining pinholes are only two results: the presence of pinholes and the absence of pinholes. However, using the test scheme in this embodiment, when light is seen to be emitted from the pinholes on the surface of the copper foil 3, it indicates that there are pinholes on the copper foil of the sample. At the same time, the number and location of pinholes can also be quickly counted and marked, which can be used to infer some problems in the production process of ultra-thin copper foil.
[0022] In this embodiment, the lining board 2 is preferably a relatively thin plate with a thickness of 2-4 mm. Each test unit 6 consumes two lining boards 2. The two lining boards 2 will soften under high temperature conditions and fully contact with the copper foil 3 under the action of pressure, and fill the pits on the surface of the copper foil 3 or flatten the wrinkles, so that the pinholes can be fully exposed, and the air between the copper foil 3 and the lining board 2 can be extracted under a vacuum state to prevent bubbles from appearing between the copper foil 3 and the lining board 2 and affecting the accuracy of the test.
[0023] The lining board 2 will automatically solidify at room temperature, so that the copper foil 3 and the lining board 2 form a whole, namely the test unit 6. The copper foil 3 will not be deformed or damaged by external forces, and the test unit 6 can be repeatedly tested and samples can be kept.
[0024] The high-temperature vacuum press can use conventional equipment on the market, which does not have high requirements. It can also use a vacuum flat vulcanizer or a vacuum hot pressing machine, which can be freely selected.
[0025] like Figure 2 As shown, the function of the pressing plate 1 is to assist in closely fitting the two lining plates with the copper foil therein. The pressing plate 1 has a larger area than the lining plate 2 and has a certain weight. For example, a 2KG steel pressing plate 1 can be used.
[0026] In this embodiment, the lining board 2 is made of polyethylene or polycarbonate, which has low material cost and can meet the effect of light transmission and high temperature softening of the lining board 2. The light transmittance of the lining board 2 is greater than 50%, and its surface flatness is less than 0.03mm, ensuring that light and sight can be seen through, and the small surface flatness can reduce the wrinkles and deformation of the surface of the copper foil 3.
[0027] In this embodiment, when the test unit 6 and the pressing plate 1 are placed together in a high-temperature vacuum press, high-temperature resistant soft pads are placed on the upper and lower sides thereof. The high-temperature resistant soft pads can prevent the pressure of the high-temperature vacuum press from damaging the lining plate 2 and the copper foil 3 products. The high-temperature resistant soft pads can be made of high-temperature resistant rubber pads or high-temperature resistant silicone pads, both of which can be purchased on the market.
[0028] In this embodiment, in step S2, the test unit 6 includes a heating stage and a heat preservation stage in the high-temperature vacuum press, which ensures that the liner 2 in the test unit 6 can be fully softened and fully fit with the surface of the copper foil 3 at a stable temperature, such as heating to 120°C at a heating rate of 10°C / min and then keeping warm for 30 minutes.
[0029] Since different colored blocks or wrinkles may appear in local areas of the front and back sides of the copper foil 3, missed pinholes may appear if only one side of the copper foil 3 is tested. Therefore, in step S3, the copper foil 3 can be placed on the window 5 with the front side facing up and the back side facing up in turn for testing, and the number and positions of the pinholes on the front and back sides of the copper foil 3 can be compared. The number and positions of the pinholes can be verified by comparing the front and back sides of the copper foil 3, thereby ensuring the accuracy of the detection.
[0030] The size of the window 5 is smaller than that of the copper foil 3, so that the light source can be prevented from being refracted through the side and affecting the pinhole judgment. At the same time, the window 5 is arranged at the top of the dark box 4, and the light source 7 is installed on the inner side wall and the bottom wall of the dark box 4. The window 5 is at the top to facilitate the placement and movement of the test unit 6. The light source 7 is arranged in this way to generate relatively uniform light emitted from the window 5, reduce reflection, and have no dead angle.
[0031] As the first specific case in this embodiment: Embodiment 1: Use a sampler to cut a copper foil 3 with a thickness of 3 μm and a size of 300*300 mm, and place it flat in the center between two lining boards 2 with a size of 350*350 mm. The lining board 2 is made of polyethylene with a transmittance of more than 50%, a thickness of 3 mm, and a smooth surface with a surface flatness of 0.03 mm.
[0032] Cover both sides of the liner 2 with a steel pressing plate 1 weighing 2 kg and measuring 370*370 mm. The pressing plate 1 is close to the polyethylene liner 2 to help the two liner 2 and the copper foil 3 fit tightly. If multiple groups of samples need to be tested, the test units are continuously stacked upwards in this structure.
[0033] Place high temperature resistant cushions on both sides of the test unit and place it in a high temperature vacuum press. Draw the vacuum to 0.05 MPa, set the pressure to 28 PSI, heat to 120°C at a rate of 10°C / min, keep warm for 30 minutes, and take it out after cooling to room temperature.
[0034] After the test sample is taken out, the outer layer of the high temperature resistant soft pad and the pressing plate 1 are peeled off. The interlayer copper foil 3 can be clearly observed through any side of the two side lining plates 2. Figure 3 As shown, it is placed at the window of the dark box with a window. The size of the window 5 is 270*270 mm, which is smaller than the cutting size of the copper foil to prevent the light source from refracting through the side and affecting the pinhole judgment. The bottom and side of the dark box 4 are equipped with light sources 7, which can be adjusted between 500-2500 lumens according to the power.
[0035] The position of the test unit 6 is adjusted until the size of the middle copper foil 3 completely covers the light source, and the number and position of the pinholes are gradually tested and counted with a light source gradient of 500, 1000, 1500, 2000, and 2500 lumens. After the test of this embodiment, the number of pinholes in the copper foil is 10.
[0036] Embodiment 2: The difference between Example 2 and Example 1 is that the thickness of the copper foil sample to be tested is adjusted, and the number of pinholes is 10, and the thickness of the copper foil 3 is 35 μm. In addition, the material of the liner 2 is changed, and a polycarbonate material is used as the liner for testing, and the light transmittance of the liner is greater than 50%. The surface flatness is 0.002 mm.
[0037] After testing, it was found that there were 10 pinholes on the surface of the copper foil.
[0038] Example 3 The difference between Example 3 and Example 1 is that the size of the copper foil sample is adjusted, and a sample with 10 pinholes and a copper foil 3 size of 500*500 mm is used for testing, a liner 2 size of 550*550 mm, and a pressure plate 1 size of 570*570 mm.
[0039] After testing, the number of pinholes on the surface of the copper foil was 10.
[0040] In contrast, the following are comparison examples without testing methods: Comparative Example 1: The difference between this comparative example 1 and the example 1 is that the copper foil test does not use the liner plate to prepare the sample. The specific process is to directly cut the copper foil to cover the window of the dark box for verification, and the copper foil is leveled by hand.
[0041] After testing, it was found that there were 15 pinholes on the surface of the copper foil, which were mainly concentrated in the wrinkled areas, and the sample could not be tested repeatedly.
[0042] Comparative Example 2: The difference between Comparative Example 1 and Example 1 is that the flatness of the lining plate is 0.5 mm.
[0043] After testing, it was found that there were 12 pinholes on the surface of the copper foil, and gas bubbles appeared between the test sample layers after pressing, which affected the sample's shielding of light and affected the observation of the number of pinholes.
[0044] Comparing the above Example 1 with Comparative Examples 1 and 2, it can be seen that the solutions of Comparative Examples 1 and 2 lead to inaccurate test results, while the results of Examples 1-3 are all accurate.
[0045] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0046] In addition, in the present invention, descriptions such as "primary", "secondary", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, features defined as "primary" or "secondary" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0047] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0048] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
Claims
1. A method for testing pinholes in ultra-thin copper foil, characterized in that: The steps include: S1: Select a copper foil (3) of standard size, and place the copper foil (3) flatly between two lining boards (2) to form a test unit (6), wherein the lining boards (2) are made of a light-transmitting material that can be softened at high temperatures, and the copper foil (3) between the layers can be observed through any side of the lining boards (2); S2: Covering the upper and lower sides of the test unit (6) with a pressing plate (1), placing the test unit (6) in a high-temperature vacuum press, and applying pressure to the upper and lower sides of the test unit (6) in a high-temperature vacuum environment; S3: The test unit (6) is taken out of the high-temperature vacuum press to cool it, the pressing plate (1) is removed, and the test unit (6) is placed together at the window (5) on the dark box (4) with a built-in light source, so that the light from the window (5) passes through the copper foil (3), and the number and position of pinholes on the surface of the copper foil (3) are obtained by testing and statistically analyzed.
2. The method for testing pinholes in ultra-thin copper foil according to claim 1, characterized in that: The lining plate (2) is made of polyethylene or polycarbonate.
3. The method for testing pinholes in ultra-thin copper foil according to claim 1, characterized in that: The light transmittance of the lining plate (2) is greater than 50%, and its surface flatness is less than 0.03 mm.
4. The method for testing pinholes in ultra-thin copper foil according to claim 1, characterized in that: When the test unit (6) and the pressing plate (1) are placed together in a high-temperature vacuum press, high-temperature resistant soft pads are placed on the upper and lower sides thereof.
5. The method for testing pinholes in ultra-thin copper foil according to claim 1, characterized in that: In step S2, the test unit (6) includes a heating stage and a heat preservation stage in the high-temperature vacuum press.
6. The method for testing pinholes in ultra-thin copper foil according to any one of claims 1 to 5, characterized in that: In step S3, the copper foil (3) is placed on the window (5) in a position with the front side facing upward and the back side facing upward in turn for testing, and the number and position of pinholes on the front side and the back side of the copper foil (3) are compared.
7. The method for testing pinholes in ultra-thin copper foil according to claim 6, characterized in that: The size of the window (5) is smaller than the size of the copper foil (3).
8. The method for testing pinholes in ultra-thin copper foil according to claim 7, characterized in that: The window (5) is arranged on the top of the dark box (4), and light sources (7) are installed on the inner side walls and bottom wall of the dark box (4).
Citation Information
Patent Citations
Overflow detection system for laminating glue solution of copper-clad laminate and use method of overflow detection system
CN117740740A
Carrier-attached ultrathin copper foil and manufacturing method for reducing pinholes of carrier-attached ultrathin copper foil
CN117888154A
Copper foil winding device capable of detecting defects
CN118566242A
Device for detecting pin-holes or tears in a foil
US6380549B1